Effects of sodium bentonite clay as a feed additive on the growth and haematology parameters of hybrid grouper, Epinephelus fuscoguttatus x Epinephelus lanceolatus - Sazmal E. Arshad; Fatin Najiha M. Jeffrey; Zarina Amin; Rossita Shapawi (Prince of Songkla University, 2021)
This study evaluated the effects of inclusion levels of sodium bentonite clay as a feed additive on growth and hematology parameters of TGGG, Epinephelus fuscoguttatus × E. lanceolatus. Four dietary treatments D1, D2, D3, and D4 feeds comprising 0, 1, 1.5, and 2% clay respectively were evaluated for weight gain (WG), specific growth rate (SGR), feed intake (FI), feed conversion ratio (FCR), survival, and hematology parameters. D3 comprising of 1.5% clay showed significantly higher WG, SGR, FI, red blood count (RBC), and the best FCR compared to the other dietary treatments. D4 comprising of 2% clay showed the least desirable effects on growth performance and feed utilization of hybrid TGGG with significantly lower WG, SGR, and RBC compared to D3; as well as the poorest FCR value. D3 also showed the lowest WBC count compared to D1, D2 and D4. Taken together, these findings indicated that dietary treatments comprising 1.5% clay is the most suitable among other investigated treatments as a growth promoting feed additive.